Peran Kehumasan Dalam Meningkatkan Efektivitas Sistem Pelayanan Informasi Di Kantor Kepala Desa Pauh Timur Kecamatan Pariaman Tengah - Syahra, Rivana Izzati; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Providing clear and accurate information is an important factor in increasing the effectiveness of the information service system in the Village Head's Office. Public Relations as one of the work units in the Village Head's Office has an important role in providing information to the community. This research aims to examine the role of public relations in improving the effectiveness of the information service system in the Office of the Head of Pauh Timur Village, Central Pariaman District, Pariaman City. This research uses qualitative methods with descriptive research type. Research data was obtained through in-depth interviews, observation and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of the research show that public relations has an important role in increasing the effectiveness of the information service system in the office of the head of Pauh Timur village, Central Pariaman District, Pariaman City.